Importance of toxicologic-chemical analysis in determining the cause of death in charred corpses - case reports - Pinterović, Bogdan; Vujović, Maja; Kostić, Emilija; Zdravković, Miodrag; Pančić, Dimitrije; Miljković, Milica; Todorović, Stevan (Archives of Pharmacy, 2022)
Determining the cause of death in charred corpses is a significant problem in forensic practice. Many delicate questions need to be answered during the autopsy of charred corpses, and one of the most important is to determine whether the corpse came into the fire alive or dead. Autopsies of three charred corpses were performed on demand of investigative authorities. External findings in all three cases revealed severe carbonization, heat defects all over the body, and numerous heat bone fractures. The internal examination discovered soot in the upper and lower airways in two cases, while the neck organs in one case were damaged and unrecognized due to heat exposure. Toxicologic-chemical analysis of the blood samples using a colorimetric method according to Wolff for carboxy-hemoglobin determination reported the following concentrations of carboxy-hemoglobin: 60%, 25%, and 10%, respectively. It was concluded that the death in all three cases was violent. However, in one case, the death occurred due to carbon monoxide poisoning (60% of carboxy-hemoglobin), while in the other two cases, the death occurs by external heat effects. Toxicologic-chemical analysis of blood for carboxy-hemoglobin above 40% is a reliable sign of carbon monoxide poisoning. Thus, it plays a significant role in determining circumstances and the cause of death in charred corpses.